Conducta obstétrica paciente secundigesta de 22 años con 30.6 semanas de gestación con preeclampsia y diabetes no controlada. - Arias España, Deysi Eliana (2022)
Preeclampsia complicates around 8% of pregnancies and is a multi-organ disease exclusive to pregnancy whose factor is pre-existing diabetes, so depending on the severity, the patient may need medication to help control her glucose levels. This clinical case study refers to a 22-year-old female patient with 30.6 weeks of gestation with severe preeclampsia plus uncontrolled diabetes. The methodology used in this clinical case is the observation and analysis of the data contained in the clinical history of the patient, who is admitted to the hospital emergency area due to presenting symptoms of 3 days of evolution, in such a way that the respective medical check-up is carried out. , whose vital signs indicate breast score 7, blood pressure 184/110, temperature 36.8, saturation 97, respiratory rate 20, with alert consciousness and proteinuria +++. During her hospitalization, the respective examinations were carried out, for the application of the adequate treatment, after a day of evolution, where each determined time the follow-up was carried out to corroborate the vital signs of the patient, she requests hospital discharge to be transferred to a hospital of greater complexity of Guasmo in Guayaquil. Obstetric management of complicated pregnancies is largely based on clinical experience, management guidelines given by the Ministry of Health of Ecuador, study data and research background, in this case there is very limited evidence from trials and research that entail preexisting uncontrolled diabetes and preeclampsia in pregnant women, in such a way that the realization of this clinical case is considered vital for the operative way of the professional obstetrician today.